Characteristics and landscape aesthetical values of heath forest - Rashidi Othman; Nur Shahira Azmi; Farah Ayuni Mohd Hatta; Qurratu Aini Mat Ali; Razanah Ramya; Wan Syibrah Hanisah Wan Sulaiman; Nur Hanie Mohd Latiff; Nursyafica Nadia Johari (Penerbit Universiti Kebangsaan Malaysia, 2023)
Heath forest is a unique ecosystem different from any other type of forest; however, its preservation has not yet been given attention even when facing a serious extinction problem. The character of this ecosystem should be studied deeper to uncover ways to prevent its extinction. Thus, integrating the heath forest characteristics in an urban area may increase awareness and appreciation of this valuable ecosystem. The main goal of this research study is to explore the uniqueness of heath forests' intrinsic values as potential attributes to be implemented in an urban context. To achieve the aim, observation of two areas of heath forest in Terengganu has been conducted to identify the characters and landscape aesthetical value. Results of the study have shown that there are many unique characteristics of heath forests that can be found despite the small scale of the study area. The characteristics can be categorised into three categories: aesthetic values according to the basic landscape elements, aesthetical values according to the landscape principle, and nature art of heath forest.